DESAIN APLIKASI TRACER STUDY BERBASIS WEB MENGGUNAKAN LARAVEL FRAMEWORK - Muhamad Yusup; Diah Aryani; Suhendi Suhendi (UNIVERSITAS RAHARJA, 2019)
Learning Evaluation conducted includes internal evaluations and external evaluations of learning management. One form of internal evaluation carried out is a comprehensive review of the curriculum. For this reason, one of them is by tracer study. Tracer Study is a tracking study conducted by alumni after graduation, which aims to find out the educational outcomes in the form of transitions from the world of higher education to the world of work, mastery of competencies, evaluation of learning processes and excavation of graduate sociobiographies. However, the availability of study data is incomplete and difficult to obtain. Some of what has been done is to use social media, e-mail and by distributing cover letters in the form of questionnaires to alumni manually. For this reason, it is necessary to develop a tracer study application with a website using Laravel Framework which has advantages, namely with MVC (model view controller) using a software approach that separates logic and presentation applications so that the time used in developing this application becomes faster.